Are novel congeneric hosts facilitating the invasion of exotic wood-boring insects? - Henri Vanhanen; Eckehard Brockerhoff (JP, 2012)
The presence and abundance of ancestral hosts or closely related species are thought to be among the main factors that facilitate successful invasions of herbivorous insects to novel environment. Invasive species have been hypothesized to follow their native host plant. We tested the host preference of Hylastes ater and Hylurgus ligniperda by using different ancestral and novel, more or less closely related coniferous hosts of Eurasian and North American origin. Both of the species are of European origin that have become established and invasive in New Zealand. These species are highly successful invaders that are now also found in several other countries, e.g. South Africa, Chile, and Uruguay. Although these are secondary bark beetles, H. ater can cause mortality of seedlings and both species contribute to sapstain of logs. Main host for both of the species in New Zealand is Monterey pine (Pinus radiata), but it is not known yet whether it is only because of the availability of the species as breeding material, since it is by far the most planted coniferous tree species in New Zealand. The host use preference and performance of H. ater has been studied by choice test in the laboratory with different coniferous and angiosperm hosts, but no large scale choice test has been made in situ. The purpose of this study was to study host preference of H. ater and H. ligniperda in situ with set up of bolts from various ancestral and novel hosts.
Keywords: Ta; vieraslaji; Montereynmänty; Pinus radiata; Uusi-Seelanti; kaarnakuoriaiset; bark beetles; invasive species